Punk Indonesia ; Songs and Lyrics Resistance - Lambok Hermanto Sihombing; Aulya Syifa Sagita; Elizabeth Octovianne Kalalo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study is aimed to explain the analysis of how resistance is used in the lyrics of punk songs. The resistance lyrics are used to give voice to the voiceless. The researchers used the data taken from the YouTube platform and analyzed it by applying Critical Discourse Analysis; Systemic Functional Linguistics (SFL) approach from Halliday. Furthermore, the results of the research showed how resistance is represented in the lyrics of the Hukum Rimba song by Marjinal and the Boikot Pemilu song by Kopral Kobong. Hukum Rimba attempted to depict actual justice that hasn’t been upheld in Indonesia, while Boikot Pemilu attempted to depict people's resistance against state officials.